Varying severity COVID-19 effects on the blood indicators of insulin-like growth factors family in patients with nonsmall cell lung cancer - O. I. Kit; E. M. Frantsiyants; D. A. Kharagezov; V. A. Bandovkina; N. D. Cheryarina; Yu. A. Pogorelova; Yu. N. Lazutin; A. G. Milakin; I. A. Leyman; O. N. Stateshny (Южно-Российский онкологический журнал, 2023)
Purpose of the study. An analysis of IGF and their carrying proteins levels in blood serum of patients with non‑small cell lung cancer (NSCLC), depending on the severity of the previous COVID-19 infection.Materials and methods. 60 patients with histologically verified NSCLC T2–3NхM0 receiving treatment at the Thoracic Department (National Medical Research Centre for Oncology, 2020–2021), were included in the study. The control group included 30 NSCLC patients after asymptomatic or mild COVID-19 disease (15 men and 15 women); the main group included 30 (15 men and 15 women) patients after severe or moderate to severe COVID-19. The mean age of patients was 59.11 ± 2.89 years. Blood counts of donors of the same age were used as the norm.Results. The levels of IGF-I, IGF-II, IGFBP2 and IGFBP3 in the blood serum of patients with NSCLC of the main and control groups were higher than those of donors by an average of 2.5, 2.1, 1.7 and 2.7 times, respectively (p < 0.05). The concentration of IGFBP1 was higher in the control group compared to the main group, and decreased in relation to donors: in the control in men and women by 1.4 and 1.9 times, and in the main group by 3.0 and 6.4 times, respectively (p < 0.05). The ratios of IGF and IGFBP1 increased in both groups: IGF-I/IGFBP1 – in the control group from 3.8 to 4.2 times, and in the main group from 7.9 to 14.4 times; IGF-II/IGFBP1 – in the control from 2.4 to 4.5 times, and in the main group from 6.6 to 12.7 times in men and women, respectively (p < 0.05).Conclusions. The level of ligands and almost all of the studied carrier proteins, except for IGFBP1, increases in the blood of patients with NSCLC of both sexes, regardless of the severity of COVID-19. The ratio of IGF-I/IGFBP1 and IGF-II/IGFBP1 in the blood increases in both groups, most significantly in the group with severe and moderate COVID-19, which indicates excessive accumulation of IGF levels and may contribute to a more aggressive course of the malignant process.